Do we know who they are? On the identity of Pholoe (Annelida: Sigalionidae: Pholoinae) species from northern Europe. Issue 1 (7th November 2019) - Meißner, Karin; Götting, Miriam; Nygren, Arne
Abstract: Pholoe species described from northern European coastal waters are studied here, based on morphological and molecular methods. We confirm the current taxonomic status of P. assimilis, P. baltica, P. inornata and P. pallida . All species descriptions are reviewed and refined, barcodes are provided allowing the identification of these species based on molecular markers. Expanding morphological methods by using confocal laser scanning microscopy has added new characters to species diagnoses and makes species identification more secure. The reliability of characters traditionally used for identification of Pholoe species is evaluated. The newly presented identification key allows the delimitation of the four species reported for European coastal waters and also includes P. minuta and P. longa . The latter have been originally described from Greenland, but were often reported from European coastal waters. The results of our studies provide new insights into the distribution of the different species. Relationships of Pholoe species from mainly northern European waters are analysed based on molecular mitochondrial and nuclear markers. We stress the need for the prospective development of a precise terminology for prostomial appendages in Pholoe by including fine anatomical studies.